2017
DOI: 10.1124/mol.117.109397
|View full text |Cite
|
Sign up to set email alerts
|

Suramin Inhibits Osteoarthritic Cartilage Degradation by Increasing Extracellular Levels of Chondroprotective Tissue Inhibitor of Metalloproteinases 3

Abstract: Osteoarthritis is a common degenerative joint disease for which no disease-modifying drugs are currently available. Attempts to treat the disease with small molecule inhibitors of the metalloproteinases that degrade the cartilage matrix have been hampered by a lack of specificity. We aimed to inhibit cartilage degradation by augmenting levels of the endogenous metalloproteinase inhibitor, tissue inhibitor of metalloproteinases (TIMP)-3, through blocking its interaction with the endocytic scavenger receptor, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Recent work suggested that the interaction of suramin and TIMP3 inhibited endocytosis of TIMP3 mediated by its interaction with the endocytic scavenger receptor, low-density lipoprotein receptor-related protein 1. 27 Although we cannot exclude additional effects of suramin on articular chondrocytes, 28–30 our data and the work of Chanalaris suggest that interaction with TIMP3 is the main mechanism involved.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Recent work suggested that the interaction of suramin and TIMP3 inhibited endocytosis of TIMP3 mediated by its interaction with the endocytic scavenger receptor, low-density lipoprotein receptor-related protein 1. 27 Although we cannot exclude additional effects of suramin on articular chondrocytes, 28–30 our data and the work of Chanalaris suggest that interaction with TIMP3 is the main mechanism involved.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, TIMP3 has the unique ability to bind to the ECM in cartilage, in contrast to the other TIMPs (TIMP1, TIMP2 and TIMP4) that diffuse freely within the matrix. 27 The N-terminus of TIMP3 contains a highly basic region that is known to interact with negatively charged sulfated ECM components. 25 26 These unique characteristics position TIMP3 as the main inhibitor of the ECM turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suramin, historically used as antiparasitic and antihelminthic drug, is able to restore the expression of chondroprotective tissue inhibitor of metalloproteinase (TIMP)-3, thereby inhibiting OA cartilage degradation by MMPs. 98 The direct inhibition of inflammation by neutralizing pro-inflammatory cytokines such as IL-1β and TNFα was less effective in OA. 99 Anti-inflammatory cytokines could antagonize proinflammatory cytokine effects.…”
Section: Therapeutically Addressed Signaling Pathways Of Oamentioning
confidence: 99%
“…Interestingly, a different therapeutic strategy involves reducing TIMP-3 binding to LRP-1, thereby increasing its level in the ECM. TIMP-3 mutants engineered to resist endocytosis have prolonged chondroprotective activity 106 , and the chemical suramin, which binds to TIMP-3 and reduces its capacity to be endocytosed, has chondroprotective effects 107 .…”
Section: Recent Advances In Mmp-13 Protein Regulation and Inhibitionmentioning
confidence: 99%